Work-related road safety: The impact of the low noise levels produced by electric vehicles according to experienced drivers. - Pardo-Ferreira, María del Carmen; Rubio-Romero, Juan Carlos; Galindo-Reyes, Fuensanta Carmen; López-Arquillos, Antonio (Elsevier, 2019)
The introduction of electric vehicles in urban areas contributes to the reduction of air and noise pollution in these environments. However, the low noise levels produced by these vehicles, previously seen as an advantage, could pose a new risk to the safety of road users. The real magnitude of this issue is, however, controversial. The present study analyses the perception of experienced electric and hybrid vehicle drivers in work situations, something which had not been studied to date. A total of 95 electric car and motorcycle drivers from different public companies in the city of Málaga, Spain, participated in the study. These drivers described risk situations with pedestrians at low speeds, especially in shared streets. They estimated that the risk caused by the low noise levels of these vehicles is “medium”. To compensate, many drivers stated that they are more alert while driving an electric vehicle. Additionally, the drivers suggested that equipping these vehicles with continuous external sound was not the most appropriate solution. In the scientific community there is no consensus on the best way to resolve this. Nevertheless, electric vehicles are now required to incorporate additional sound in the European Union and USA. This does not mean that this is a more effective solution. More research on this issue is thus needed, such as studying other non-acoustic solutions or analysing how other road users perceive the risk.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16957
Keywords: Vehículos eléctricos - Gestión del riesgo; Percepción del riesgo; Seguridad vial; Electric vehicles; Risk perception; Experienced drivers; Work-related road safety; Low noise